Programa BPC na escola : dilemas e perspectivas no campo dos direitos sociais - Cunha, Monica Isabel Carleti (2015)
The overall study objective is to analyze the interface between education and social assistance, focusing on the local management dynamics of the Continuous Accountability Benefit Program in the School, located in the municipality of VitoriaES. It is an intersectoral program that aims to identify and act in overcoming boundaries that may affect the process of education for children and adolescents with disabilities living in extreme poverty. In this research, we list the following specific objectives: To understand aspects of the constitution of the municipal management committee; Characterize the dynamics of work and assignments of duties between members of municipal management committee; Identify the actions indicated by the local steering committee for overcoming barriers to access and retention of students with disabilities in regular education. The theoretical and methodological support is based on figurational theory by Norbert Elias, which puts the social processes in permanent constitution through social networks in which different directions of "events" social stem from the balance generated on established relationships in human settings. In this study, the case study methodological design has been applied, it was developed through the analysis of legal and normative documents; reports and interviews with members of the management Programme committee. In the analysis section, it is observed that, historically, the school has occupied an important social role as implementing agency of social programs that discover the poor and disabled, conforming them to citizenship produced by a specific bourgeois ethos. It is understood that the "Continuous Accountability Benefit" should be considered as a right to social protection. Just as the "Continuous Accountability Benefit", the program "Continued Accountability Benefit in School" must be committed to the guarantee of the basic education rights and should not be handle as a service of productive inclusion for students with disabilities, in which people's access employment overlaps with their access to knowledge historically accumulated by humanity. We also note that neoliberal policies, based on market discipline, bring immediate implications in the activities of the management committee, whose members meet multiple duties and representations. Associated with this, we see a significant turnover of the members of that committee which causes difficulties in implementing policies focused on the demands of the disabled. We also note that in addition to legal provisions that support the cross-sectoral goal of the management committee, defining its functions and tasks, the municipal administration must be committed to an agenda planned on implementation and evaluation of social policies.